Analysis of the Indonesian Language Proficiency Test of Muhammadiyah Vocational High School Students in Sukabumi - Hera Wahdah Humaira; Asep Firdaus (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to analyze the Indonesian language proficiency of students at Muhammadiyah Vocational High School (SMK) Sukabumi through the Indonesian Language Proficiency Test (UKBI). Previous studies have mainly focused only on reading proficiency at the senior high school level, whereas this research covers overall language competence, differences in performance across the domains of listening, grammatical response, and reading, the factors influencing test results, and their relevance to Indonesian language learning needs at the vocational level. This research employed a quantitative descriptive method, involving 46 students as participants. Data were collected through a manual UKBI using a paper-based test format. The results show that the majority of students fall into the Intermediate (Semenjana) category (60.87%) and Marginal category (17.39%), while only 6.52% achieved the Excellent (Unggul) level. Domain analysis revealed that listening skills were relatively stronger, while reading and grammatical response skills were lower. Factors influencing performance included learning motivation, literacy exposure, teaching methods, social background, and everyday language use. This study highlights the importance of implementing literacy-based learning and practical language use to improve the language competence of vocational students.